2
$\begingroup$

A loan for $8,000$ must be repaid with 6 year end payments at an annual rate of $11 \%$. What is the annual payment? I know that the present value of an annuity with end payments is $\frac{1-v^n}{i}$ where $v = 1/(1+i)$. Likewise, the future value is $(1+i)^{n}\frac{1-v^n}{i}$. How do I use this to solve this problem?

$\endgroup$
  • $\begingroup$ Isn't it just that you want the present value of the annuity to equal the loan amount? Excel's PMT will let you check your answer $\endgroup$ – Ross Millikan Oct 15 '10 at 20:23
  • $\begingroup$ How do you get the present value? I know $PV = \frac{FV}{(1+i)^n}$. But how yould you formulate this in terms of annuities? How do you do it by hand? $\endgroup$ – PrimeNumber Oct 15 '10 at 20:30
2
$\begingroup$

We have to find the value of constant (I assume, since nothing is specified on the contrary) payments $A$ given the principal $P$ during $n$ yearly periods and the interest rate $i$. The value of $A$ in the period $k$ is equivalent to the present value $A/\left( 1+i\right) ^{k}$ monetary units, where $i$ is the interest rate in each capitalization period. Summing in $k$, from 1 to $n$, we get the sum

$$\displaystyle\sum_{k=1}^{n}\dfrac{A}{\left( 1+i\right) ^{k}}$$

This is a geometric progression with ratio $r=1/(1+i)$ and first term $u_{1}=A/\left( 1+i\right)$ whose sum is:

$$\dfrac{A}{1+i}\dfrac{\left( \dfrac{1}{1+i}\right)^{n}-1}{\dfrac{1}{1+i}-1}=A\dfrac{\left( 1+i\right) ^{n}-1}{i\left( 1+i\right) ^{n}}=P.$$

Hence

$$A=P\dfrac{i\left( 1+i\right) ^{n}}{\left( 1+i\right) ^{n}-1}.$$

For the given problem, the payments will be made during $n=6$ years, with $i=11\%=\dfrac{11}{100}$ and $P=8000$:

$$A=8000\times \dfrac{0.11(1.11)^{6}}{(1.11)^{6}-1}\approx 1891$$


Sum of a geometric progression:

$$S=u_{1}+u_{2}+u_{3}+\ldots +u_{n}$$

$$rS=ru_{1}+ru_{2}+ru_{3}+\ldots +ru_{n-1}+ru_{n}$$

$$u_{k}=ru_{k-1}=u_{1}r^{k-1}$$

$$S-rS=\left( u_{1}+u_{2}+u_{3}+\ldots +u_{n}\right) -\left( ru_{1}+ru_{2}+ru_{3}+\ldots +ru_{n-1}+ru_{n}\right) $$

$$(1-r)S=u_{1}-ru_{n}$$

$$S=\dfrac{u_{1}-ru_{n}}{1-r}=\dfrac{u_{1}-u_{1}r^{n}}{1-r}=u_1\times\dfrac{1-r^{n}}{1-r}=u_1\times\dfrac{r^{n}-1}{r-1}.$$

$\endgroup$
  • $\begingroup$ How did you sum the geometric series? I thought $\sum_{k=m}^{n} ar^{k} = \frac{a(r^{m}-r^{n+1})}{1-r}$. $\endgroup$ – PrimeNumber Oct 16 '10 at 18:16
  • $\begingroup$ The sum of the geometric progression (starting at order $n=1$ until $n$) $u_{1}$, $u_{2}$, $\ldots$ ,$u_{n}$ is $S=u_{1}\times \dfrac{1-r^{n}}{1-r}$, where $r$ is the progression ratio. $\endgroup$ – Américo Tavares Oct 16 '10 at 18:32
  • $\begingroup$ @Trevor: I added the derivation of the progression sum formula. $\endgroup$ – Américo Tavares Oct 16 '10 at 18:49

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.